Endemic species have highly integrated phenotypes, environmental distributions and phenotype–environment relationships. (8th March 2013) - Hermant, Marie; Prinzing, Andreas; Vernon, Philippe; Convey, Peter; Hennion, Françoise
Abstract: Aim: Why are some species geographically restricted? Ecological explanations suggest that endemic species may have restricted distributions because limited phenotypic variability results in narrow niches. However, studying variability of traits independently may not fully explain the interactions within and between complex phenotypes and environments. Here, we hypothesize that endemic species are restricted to a narrow range of habitats due to strong phenotypic integration (i.e. strong correlations among traits), strong environmental integration (i.e. strong correlations among the environments occupied) and strong correlations among trait–environment combinations. Location: The Kerguelen Islands, sub‐Antarctic. Methods: We measured flowering phenology, multiple morphological characters, and species distribution along three abiotic environmental gradients (elevation, soil moisture and soil salinity) in 14 plant species whose distributions range from strictly endemic to cosmopolitan. Results: We found that for individual species, trait means and variances were independent of endemism, but that endemics occupied higher and less variable microhabitats. However, phenotypic integration, environmental integration along the three gradients, and the strength of trait–environment correlations all increased with the level of species endemism. Main conclusions: Higher levels of integration within and between phenotypes and environments are associated with more restricted geographical ranges in the species studied. In endemic species phenotypic integration may explain range contraction during the taxon cycle and reduce the ability to adapt to novel microhabitats formed as a result of environmental change.